Brunner’s Glands Hyperplasia: Diagnosis with EUS-FNA for Suspected Pancreatic Tumor Involving the Duodenum - Arena, Monica; Rossi, Stefania; Morandi, Elisabetta; Mangiavillano, Benedetto; Franchi, Paolo (JOP. Journal of the Pancreas, 2012)
Context Brunner’s gland hyperplasia is a rare, benign, proliferative disorder of the duodenum. Large masses may cause obstructive and compressive symptoms which may depend upon the location of the tumour. Owing to its rarity, these lesions can be mistaken for malignancy on radiological and endoscopic examinations. Symptomatic Brunner’s gland hyperplasia associated with pancreatitis is very rare and the literature is limited to a few case reports endoscopic ultrasound may be useful to obtain a correct diagnosis. Case report We describe an unusual case of diffuse Brunner’s gland hyperplasia of duodenum mimicking a malignancy involving the pancreas, in which EUS-FNA avoided a possible major surgery. Conclusion Brunner’s gland hyperplasia imaging is very similar to malignant pancreatic mass; EUS with FNA is mandatory to reach a correct diagnosis, avoiding surgery. Image: Endoscopic findings of duodenal sub-stenosis.